دراسة تحليلية للإصابات الرياضية الأكثر شيوعًا في حصص التربية البدنية للطور الابتدائي - بلعيد إبراهيم; بن شريف ياسين (My University, 2025)
تهدف الدراسة إلى التعرف على الإصابات الرياضية الأكثر شيوعًا بين تلاميذ الطور الابتدائي خلال حصص التربية البدنية والرياضية، ولهذا الغرض استخدمنا منهج الوصفي على عينة متكونة من 50 أستاذ للتربية البدنية والرياضية للتعليم الإبتدائي لولاية الأغواط للموسم الدراسي 2024/2025 تم اختيارها بشكل عشوائي، لجمع البيانات استخدمنا استمارة الاستبيان، بعد جمع النتائج ومعالجتها إحصائيا تم التوصل إلى النتائج الإصابات الرياضية الأكثر شيوعًا بين تلاميذ الطور الابتدائي خلال حصص التربية البدنية هي الإصابات الطفيفة والمتوسطة والشديدة. وعلى هذا الأساس أوصت الدراسة بضرورة توفير مساحات كافية لممارسة الأنشطة الرياضية، وتقليل عدد التلاميذ داخل كل فوج لضمان مساحة كافية للحركة الآمنة.
دراسة ميدانية على أساتذة التربية البدنية والرياضية للتعليم الإبتدائي لولاية الاغواط
The Object of the study aims to identify The most common sports injuries among primary school students during physical education and sports classes, for this purpose, we used the method Descriptive On a sample composed of 50 physical education and sports teachers for primary education in Laghouat province for the 2024/2025 academic year Chosen as random, and for data collection, we used a tool Questionnaire .After collecting the results and having treated them statistically, we conclude The most common sports injuries among elementary school students during physical education classes are minor, moderate, and severe injuries. On this basis, the study recommended It is necessary to provide sufficient spaces for practicing sports activities, and to reduce the number of students in each group to ensure sufficient space for safe movement.